Blood donors' motivation and attitude to non-remunerated blood donation in Lithuania - Blazeviciene Aurelija; Stonienë Laimutë; Buciuniene Ilona; Kazlauskaite Ruta; Skudiene Vida (BMC, 2006)
Abstract Background In the Soviet period, the blood donation system operated in Lithuania exclusively on a remunerative basis. After joining the EU, Lithuania committed itself to meeting the EU requirements to provide all consumers within its boundaries with safe blood products made from voluntary unpaid blood donations. However, the introduction of a non-remunerated donation system may considerably affect donors' motivation and retention. Thus the aim of the current research was to determine blood donation motives among the present donors and investigate their attitude towards non-remunerated donation. Methods A questionnaire survey of 400 blood donors. Survey data processed using SPSS statistical analysis package. Statistical data reliability checked using Fisher's exact test (p < 0.05). Results Paid donors comprised 89.9%, while non-paid ones made 10.1% of the respondents. Research findings show that 93 per cent of the paid donors give blood on a regular basis; while among the non-remunerated donors the same figure amounted merely to 20.6 per cent. The idea of the remuneration necessity is supported by 78.3 per cent of the paid donors, while 64.7 per cent of the non-remunerated respondents believe that remuneration is not necessary. The absolute majority of the paid donors (92%) think they should be offered a monetary compensation for blood donation, while more than half of the non-remunerated donors (55.9) claim they would be content with a mere appreciation of the act. Provided no remuneration were offered, 28.44 per cent of the respondents would carry on doing it, 29.6 per cent would do it only in emergency, 29.6 per cent would donate blood merely for their family or friends, and 12.3 per cent would quit it completely. Conclusion Most respondents admitted having donated blood for the following reasons: willingness to help the ill or monetary compensation. Majority would consent to free blood donation only in case of emergency or as a family replacement, which leads to a conclusion that provided monetary remuneration is completely terminated part of the currently active paid donors would withdraw from this activity, which might seriously affect the national supply of blood and its products.